Emissions Trading Registries : Guidance on Regulation, Development and Administration - Partnership for Market Readiness (World Bank, Washington, DC, 2016)
The issues around the environmental integrity of international market mechanisms have gained a great deal of attention in the wake of the Paris Agreement. In addition, with the agreement on market-based measures for international aviation being reached, these issues are likely to gain even more prominence in countries’ efforts to prepare for the implementation of international market mechanisms. In a context where inaccurate accounting is one of the environmental integrity risks associated with market mechanisms, an emissions trading registry is critical for avoiding “double counting”—the situation where a single GHG emission reduction or removal is used more than once to demonstrate compliance with mitigation targets. An emissions trading registry is an online database that issues, records, and tracks the carbon units that are exchanged within market mechanisms or financed through Results-Based Climate Finance programs. Given the length of time and capacity needed for the development of a registry, it is essential for countries that are in the process of designing market mechanisms to factor in specific regulatory, administrative, functional, and technical aspects of registry development. Against this backdrop, and to further facilitate future registry design and implementation, this report provides policy makers and other stakeholders with technical insights and guidance on how to support country-specific decision making and activities related to registry development.